BVRI PHOTOELECTRIC PHOTOMETRY FOR 275 STARS LOCATED BETWEEN 25 Y 50 - IRIARTE ERRO, B (Observatorio Astrofísico de Tonantzintla, Pue, Pue, Mex, 1967)
BYRI photometry in Johnson's system was done for 275 stars the mayority of which are comprised between -25° and -50°. Due to systematic variations in V magnitude in R. A. of the order of 0.2 magnitude it was decided to use in the present work V magnitudes
BOL OBS TONAN TACUB
Keywords: PHOTOELECTRIC, PHOTOMETRY; ASTRONOMIA Y ASTROFISICA; ASTRONOMIA OPTICA; FOTOELECTRICA